(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Electric Vehicle Charging Stations (EVCS) have become a critical component of modern energy infrastructure as the adoption of electric vehicles (EVs) continues to grow rapidly. While these stations are essential for facilitating the transition to sustainable transportation, their widespread integration into the power grid presents significant challenges related to power quality. Given the increasing number of EVCS installations globally, the paper highlights the need for comprehensive studies of their impact on the existing power grid and mitigation strategies to ensure that power quality standards are maintained to support the seamless integration of EVs. Unlike other reviews that focus on a specific power quality like harmonics, this review makes a distinct contribution to the literature by providing a comprehensive analysis of the six major power quality disturbances with EVCS, such as harmonics distortion, voltage sags, transformer loading, voltage fluctuations, power factor, and phase imbalance. The paper also delves deeper into the variation of power quality disturbances with the EV penetration levels, the power quality disturbances, particularly transformer loading increases with the power of the EV charger, higher derating of the transformer required to accommodate a higher number of EVs, and voltage sags increase more during the peak hours and increase with the penetration level of EVs. Finally, mitigation strategies are proposed in the discussion section of the paper, such as the adoption of vehicle-to-grid technologies, integration of energy storage systems, and integration of distributed renewable energy sources to reduce the negative effects of EVCS on power quality while ensuring a smooth transition to an electric transportation future.